PERENCANAAN PAKET WISATA BUDAYA DI DESA KESIMAN KECAMATAN DENPASAR TIMUR - Pradnya Sutara, I Made; Suwena, I Ketut; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
Bali have one city, it is Denpasar City, within tourism potencies that can be build to be package tours. Kesiman Traditional Village is one of many villages in Denpasar City that has many tourism potency, the potency is cultural tourism potencies that can be found, such as : art attraction, historical place, traditional fashion and food, villager activities based on culture, hospitality of the villagers. Those cultural Potencies which found in Kesiman Traditional Village can be pack to be cultural package tours. Regard to planning cultural package tour, the formulation of issues are : (1) What is the potencies that can be found in Kesiman Traditional Village, East Denpasar? (2) How the planning cultural package in Kesiman Traditional Village? The technique to collecting data did through observation, interviews, documentation, and books literature. The result of the research is known that Kesiman Traditional Village has cultural tourism potencies and those potencies can be package into cultural package tour, those are : Barong and Keris Dance, Wadah Maker, Pengrebongan Temple, Kesiman Castle, Odah Turut Balinese House, Balinese Dance and Music Lesson in Bale Banjar Ceramcam Kesiman, Made Sudyatmika Paint Lesson, Ananda Balinese Boutique, Kertalangu Tourist Village with jogging track surrounded by rice field, fishing pond, and World Peace Gong, and Kroya Kites House. Those potencies then package into planning cultural package tour in the form of tables, essay, and graphic. Those are package into cultural package tour, those are : (1) History and Spirit of Kesiman Cultural Tour, (2) Beautiful Art of Kesiman Cultural Tour, (3) Art and Local Activities of Kesiman Cultural Tour.
Keywords: Potencies, Cultural Tourism, Package Tour